2008
DOI: 10.1002/ps.1628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fungicide systemicity in wheat using LC‐MS/MS

Abstract: BACKGROUND: Systemicity is an important attribute of fungicides that is difficult to measure in early-stage screening without labeling the compound with a radioisotope. A method of measuring translocation that does not require potent fungicidal activity or a radiolabel would guide identification of compounds with desirable attributes. RESULTS:The authors developed an analytical technique that mimics field application, using LC-MS/MS to screen compounds for translocation in wheat leaves. The method sorted comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The AI contents of the ears and flag leaf blades decreased as the sampling time lengthened and showed first‐order kinetics, in agreement with the findings of other studies . The slopes of the first‐order kinetics curves indicated that the metabolism in the ears (Table ) was slowest in GK Fény for both AIs, but there were much smaller differences between the cultivars in 2011 than in 2010.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The AI contents of the ears and flag leaf blades decreased as the sampling time lengthened and showed first‐order kinetics, in agreement with the findings of other studies . The slopes of the first‐order kinetics curves indicated that the metabolism in the ears (Table ) was slowest in GK Fény for both AIs, but there were much smaller differences between the cultivars in 2011 than in 2010.…”
Section: Resultssupporting
confidence: 90%
“…Besides radiolabelled AIs and biotests, both gas and liquid chromatography coupled with (tandem) mass spectrometry (GC/MS, LC/MS and LC/MS/MS) are used to investigate the translocation ability of pesticides. Klittich et al . developed an LC/MS/MS method for the assessment of fungicide systemicity in wheat, and found differences in the translocation properties of AIs within two‐leaf‐stage seedlings at distances of 0.5–3 cm from the application zone.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of lipophilicity on fungicides was first discussed by Briggs . In a study using liquid chromatography–tandem mass spectrometry (LC‐MS/MS) to examine fungicide systemicity in whole plants, lipophilicity was found by Klittich et al . to be a significant factor for prediction of foliar systemicity when using a drop‐line fungicide application.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The effect of lipophilicity on fungicides was first discussed by Briggs. 11 In a study using liquid chromatography-tandem mass spectrometry (LC-MS/MS) to examine fungicide systemicity in whole plants, lipophilicity was found by Klittich et al 40 to be a significant factor for prediction of foliar systemicity when using a drop-line fungicide application. A more recent study looked at the effects of several physicochemical properties, including lipophilicity, WS, melting point and molar volume, on the translaminar activity of fungicides; again, greater lipophilicity was found to correlate with decreased translaminar movement.…”
Section: Lipophilicitymentioning
confidence: 99%
“…Abundant evidence strongly supports the view that agricultural use of azoles led to pan-azole clinical resistance (11, 14, 18), including genetic similarities in azole-resistant A. fumigatus isolates from agricultural settings where azoles are used as fungicides and from clinical settings where azoles are used as drugs (14) and the presence in clinical isolates of markers for resistance to fungicides only used in agriculture (11). Resistance to clinical azole drugs has been reported in the U.S. (13) where azoles are also used as agricultural fungicides (4, 10); however, information about the presence of azole-resistant A. fumigatus in agricultural environments in the U.S. has been limited. Environmental sampling of a cull pile from a single agricultural site in Georgia yielded the first environmental TR A. fumigatus strains identified in the U.S. (20).…”
Section: Introductionmentioning
confidence: 99%